13P MDSC (myeloid-derived suppressor cells) is an important immunosuppressing factor and functionally related with VEGF and IL-17 in patients with gastrointestinal cancer. (15th December 2019) - Shibata, M; Nakajima, T; Mimura, K; Shimura, T; Kono, K; Takenoshita, S
Abstract: Background: Immune checkpoint inhibitors have been reported to be ineffective in patients with high levels of MDSC (myeloid-derived suppressor cells) and MDSC has been proven to be stimulated by inflammation involving VEGF and IL-17. We have reported that MDSC, IL-17 and VEGF are closely associated with immunosuppression and poor prognosis. Methods: Stimulation index (SI) obtained by PHA-blastogenic response of lymphocyte was used as a marker of cell-mediated immunity and was tested in 658 patients with unresectable diseases including 260 esophageal, 110 gastric and 288 colorectal cancers. These patients received chemotherapy and SI were analyzed in correlation with nutritional status, treatment outcome (RECIST) and prognosis. These patients were divided into 2 groups with a median level of SI and, chemotherapy outcome and overall survival were compared between these groups (Study 1). To characterize the mechanisms of immunosuppression, PBMC (peripheral blood cells) were separated from the patients and the production of IL-17 (ELISA) by PBMC. Circulating levels of MDSC (CD14-CD11b+CD33+/flow cytometry), serum levels of VEGF (ELISA) were measured and analyzed in 43 patients with gastric cancer and 64 with colorectal cancer (Study 2). Results: (Study 1) The overall survival was significantly worse in patients with lower SI than in those with higher SI in each disease, and the responses (RECIST) to chemotherapy were significantly better in patients with higher SI than those with lower SI. SI were significantly inversely correlated with NLR (neutrophil/lymphocyte ratio: inflammatory parameter) and nutritional factors including prealbumin, retinol-binding protein and transferrin. (Study 2) SI were significantly and inversely correlated with the levels of MDSC, the production of IL-17, and the levels of VEGF. The levels of MDSC, VEGF, IL-17 were significantly correlated with each other and inversely with nutritional parameters. Conclusion: The key mechanisms of immunosuppression in these patients are systemic inflammation involving MDSC, VEGF and IL-17. Immune checkpoint inhibitors might be more effective with a decreased MDSC by controlling VEGF and IL-17. Legal entity responsible for the study: Masahiko Shibata. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.